Exploring practical experience with different treatments in NSCLC patients with MET-deregulated: a retrospective analysis from the real world - Mengmeng Li; Jiuyan Huang; Ruyue Xing; Xinyang Du; Chunhua Wei; Huijuan Wang (BMC Pulmonary Medicine)
Abstract Background Mesenchymal to epithelial transition factor (MET) dysregulation in non-small-cell-lung-cancer (NSCLC) is understudied, with scant data on treatment outcomes. Methods We retrospectively examined 160 NSCLC patients: 125 with primary MET mutations (further classified into MET exon 14 (METex14) skipping mutations and primary MET amplifications) and 35 with secondary MET amplifications. Patients underwent varied treatments: Chemotherapy, Immune monotherapy, Crizotinib, or Savolitinib. Secondary MET amplification patients were grouped by treatment: Group A (Class Ib MET-TKI with third-generation EGFR-TKI), Group B (Crizotinib with first-generation EGFR-TKI), and Group C (Crizotinib alone). One hundred and thirty patients have completed the whole treatment process. Their data were included in the study's survival analysis (included 95 patients with primary MET mutations and 35 patients with secondary MET amplifications). Results Among METex14 skipping mutations patients (n = 57), median progression free survival (PFS) was: Chemotherapy 7.64 m, Crizotinib 8.5 m, Savolitinib 9.3 m, and Immunotherapy 3.87 m. Targeted therapies and chemotherapy significantly outperformed Immunotherapy. Sub-group analysis indicated splice donor region mutations benefited more than those at the polypyrimidine tract (9.23 m vs. 4.03 m, P = 0.038). For primary MET amplifications (n = 38), PFS was: Chemotherapy 2.84 m, Crizotinib 3.80 m, Savolitinib 5.23 m, and Immunotherapy 3.30 m. Patients with copy number (CN) > 5 had longer PFS than CN ≤ 5 (5.17 m vs. 3.44 m, P = 0.039). In secondary MET amplifications (n = 35), Group A and B had similar PFS (6.77 m and 6.57 m) versus Group C (3.13 m). Dual-target therapy PFS showed no difference between CN ≤ 5 and CN > 5 (8.63 m vs. 6.27 m, P = 0.29). Conclusion NSCLC patients with METex14 skipping mutations benefit more from targeted therapies, especially those with splice donor mutations. MET amplification patients benefit universally from targeted therapies; primary MET amplifications show higher benefits with increased copy numbers. For secondary MET amplifications post-EGFR-TKI resistance, dual-target therapy surpasses Crizotinib monotherapy, independent of MET copy number.